2015
DOI: 10.1055/s-0034-1391666
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bile duct cancer by bile cytology: usefulness of post-brushing biliary lavage fluid

Abstract: Background: Pathologic evidence of biliary diseases can be obtained from cytology in addition to endoscopic retrograde cholangiopancreatography (ERCP); however, the diagnostic effectiveness is not satisfactory. Study aim: This retrospective, single-center study evaluated the efficacy of various sampling methods for the cytologic diagnosis of bile duct cancer. Patients and methods: Biliary samples included bile that was simply aspirated, brush smear, brush-rinsed saline, and post-brushing biliary lavage fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…Because cholangiocarcinoma is the most common malignant tumor of the biliary tree (approximately 80% of cases), cytologic findings suspicious of malignancy include dyscohesive/loose three‐dimensional cell clusters, loss of honeycomb pattern characteristic of benign epithelium, increased N/C ratio, nuclear molding/indentation, nuclear enlargement and pleomorphism, coarse/clumped chromatin, irregular nuclear contours, macronucleoli, loss of nuclear‐cytoplasmic polarity, and necrotic background . However, the sensitivity for the diagnosis of biliary cancer is unsatisfactory although several ancillary techniques such as DNA histogram or fluorescence in situ hybridization of chromosomes 3, 7, 9, 17 have been applied to improve the yield of brush cytology. Sugimoto et al reported that the use of brush‐rinsed saline and postbrushing biliary lavage fluid improved the sensitivity by increasing the cellular component in the sample .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because cholangiocarcinoma is the most common malignant tumor of the biliary tree (approximately 80% of cases), cytologic findings suspicious of malignancy include dyscohesive/loose three‐dimensional cell clusters, loss of honeycomb pattern characteristic of benign epithelium, increased N/C ratio, nuclear molding/indentation, nuclear enlargement and pleomorphism, coarse/clumped chromatin, irregular nuclear contours, macronucleoli, loss of nuclear‐cytoplasmic polarity, and necrotic background . However, the sensitivity for the diagnosis of biliary cancer is unsatisfactory although several ancillary techniques such as DNA histogram or fluorescence in situ hybridization of chromosomes 3, 7, 9, 17 have been applied to improve the yield of brush cytology. Sugimoto et al reported that the use of brush‐rinsed saline and postbrushing biliary lavage fluid improved the sensitivity by increasing the cellular component in the sample .…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity for the diagnosis of biliary cancer is unsatisfactory although several ancillary techniques such as DNA histogram or fluorescence in situ hybridization of chromosomes 3, 7, 9, 17 have been applied to improve the yield of brush cytology. Sugimoto et al reported that the use of brush‐rinsed saline and postbrushing biliary lavage fluid improved the sensitivity by increasing the cellular component in the sample . In addition, they described that the efficacy of cytology for detecting tumors is related to wider intramucosal tumor spread and intraluminal protruding tumor growth .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Balloon predilation was previously reported to significantly improve the diagnostic yield of BC [8]. Sugimoto et al [26] recently reported that the diagnostic efficacy of cytological evaluation of post-brushing biliary lavage fluid was superior to that of BC in bile duct cancer (75% vs. 49%). We predict that the effect of lavage followed by dilation/distortion by SpyGlass  might be comparable to that achieved by predilation or post-brushing lavage.…”
Section: Discussionmentioning
confidence: 99%